Instantaneous messaging system: a distributed approach - García, Pablo S. (2001)
This work presents the development of an instantaneous messaging system, which is centered on the distributed handling of user groups. The method pro-posed for handling of groups has several distinctive characteristics: the non exis-tence of a moderator for each group, allowing any user to abandon the group at any moment without putting in danger the group's existence, and the absence of a server where the user must be authenticated every time that he wants to engage in conversation with somebody, which allows that a more direct communication be established with the person with which communication is desired.